Diagnostic Accuracy of Elevated Neutrophil: Lymphocyte Ratio (NLR) and Platelet: Lymphocyte Ratio (PLR) for the Prediction of 28-Day Mortality in Patients Presenting with Acute Exacerbation of COPD at Tertiary Care Hospital, Karachi: NLR and PLR in AECOPD Mortality - Ahmed, Aftab; Asad, Faisal; Shaikh, Nida; Nouman, Rabeea; Sikander, Komal; Ahmed, Muzamil (Pakistan Journal of Health Sciences, 2026)
Chronic obstructive pulmonary disease (COPD) patients experiencing sudden flare-ups and immediate risk of death, and basic inflammatory indicators may assist in early risk assessment. Objectives: To assess the diagnostic performance of elevated neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in predicting 28-day mortality among patients presenting with acute exacerbations of chronic obstructive pulmonary disease. Methods: The study was a prospective observational cohort study conducted at the Ojha Institute of Chest Diseases, Karachi (June 2025 to November 2025), following ethical approval. 88 AECOPD patients aged 20-70 years were recruited through consecutive sampling. Complete blood counts were used to calculate baseline NLR and PLR, which had predetermined cutoffs (>6.74 and >203.6). Mortality within 28 days was tracked among patients. Data analysis was done using SPSS version 25.0. Sensitivity, specificity, and ROC curves, along with multivariate logistic regression with confounder adjustments, were used to assess prognostic performance. Results: Among 88 AECOPD patients, the mean age was 61.16 ± 9.89 years, and 26 (29.5%) died within 28 days. Elevated NLR (84.1%) and PLR (78.4%) were common. The sensitivity of NLR was higher (80.77%), whereas its specificity (14.52%) and prognostic value (AUC 0.58) were lower, and the performance of PLR was poorer (AUC 0.52). Subgroup analysis indicated a better performance among older patients. In general, both biomarkers showed less than optimal prognostic value for 28-day mortality, with NLR being slightly better than PLR. Conclusions: While increased NLR and PLR were typical findings in acute COPD exacerbations, they showed poor diagnostic utility for forecasting 28-day mortality.